2008
DOI: 10.1139/x07-155
|View full text |Cite
|
Sign up to set email alerts
|

Long-term spatial and structural dynamics in Acadian mixedwood stands managed under various silvicultural systems

Abstract: Using inventory data from a long-term silviculture experiment in east-central Maine, spatial models were developed to analyze 28 years (1974–2002) of stand structural dynamics. Differences in spatial pattern, species mingling, height differentiation, and relative stand complexity index (rSCI) were compared among five treatments: commercial clear-cutting, fixed diameter-limit, 5 year single-tree selection, three-stage shelterwood (both with and without precommercial thinning), and unharvested natural areas. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…The selection method usually produces more complex forest structures than those generated by the shelterwood method and, additionally, better resembles the dynamics found in untreated natural areas (Saunders and Wagner, 2008). Similarly, the diameter distributions found in Navahonda should be considered better models in the search for a sustainable silviculture able to maintain biodiversity in Pinus nigra stands.…”
Section: Discussionmentioning
confidence: 99%
“…The selection method usually produces more complex forest structures than those generated by the shelterwood method and, additionally, better resembles the dynamics found in untreated natural areas (Saunders and Wagner, 2008). Similarly, the diameter distributions found in Navahonda should be considered better models in the search for a sustainable silviculture able to maintain biodiversity in Pinus nigra stands.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research by Proulx and Parrot (2008), the most complex patterns were shown to be represented by intermediate values of MIG. Traditionally, digital cameras record pictures in RGB (Red Green Blue) format, but for a more direct link to the actual colour of objects and effects of light, our photographs were converted to HSB images (Hue Saturation Brightness) following the method proposed by Smith (1978). Each pixel in the image thus bears three values respectively defining its colour (hue), the intensity of the colour (saturation) and the quantity of light it received (brightness).…”
Section: Photographs Samplingmentioning
confidence: 99%
“…Instead, earlier studies have looked at the relationship between species and structural diversity. Years of study have thus led to knowledge of the response of specific structures such as living trees (Crow et al 2002, Brais et al 2004, Saunders and Wagner 2008, dead wood, (McGee et al 1999) and understory plants (Roberts 2007) to different types of harvesting. On the other hand, the effects of partial cuts on the spatial distribution of structure and habitat heterogeneity have also been studied for different animal taxa (Suzuki and Hayes 2003, Loehle et al 2005, AguilarAmuchastegui and Henebry 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In natural stands, where human activity is limited to the minimum, this diversity is usually much greater than in commercial forests, which are often even-aged and a single species. In the latter, diversity can be shaped indirectly by using proper treatments (Pretzsch 1996(Pretzsch , 1999Hanewinkel 2004;Saunders, Wagner 2008;Jaworski 2013). There is, of course, no option to abandon precommercial treatments in these forests, but one can discuss methods applied depending on the species and commercial purposes.…”
Section: Introductionmentioning
confidence: 99%